Optimal Investment and Technical Progress - Chakravarty, S. (Review of Economic Studies, 1964)
Journal Article Optimal Investment and Technical Progress Get access S. Chakravarty S. Chakravarty Delhi University Search for other works by this author on: Oxford Academic Google Scholar The Review of Economic Studies, Volume 31, Issue 3, June 1964, Pages 203–206, https://doi.org/10.2307/2295909 Published: 01 June 1964